INTERNALISASI NILAI-NILAI KEISLAMAN DALAM SKEMA HIDDEN CURRICULUM DI MTS NURUL HUDA MEDINI DEMAK (Program Studi Pendidikan Agama Islam, 2017)
INTERNALIZATION OF ISLAMIC VALUE IN HIDDEN CURRICULUM SCHEMA IN MTs Nurul Huda Medini Demak. This study aims to know the internalization of Islamic values on students through hidden curriculum activities at MTs Nurul Huda Medini. This study used a qualitative approach and the data were collected through observations, interviews, documentations and field notes. Informants in this study are the headmaster, the deputy head of the curriculum and students. The research concludes that in the midst of modernity today, there is a tendency of the negative influence for learners in their behavior. It is because the rapid of technology development which influenced the students’ social negative actions. To anticipate it, the part of education institution (MTs Nurul Huda) Medini has a responsibility by habituating the high values trough some activities which are able to bring a positive influence for the students. For instance, habiatuate to do smile, give salutation, and greet, read the Asma’ul Husna every morning, praying dhuha and dhuhur in congregation, read tahlil every Thursday, the application of uniform, and park management.